Clinical Outcomes of Tibial Components with Modular Stems Used in Primary TKA - Nicole Durig; Thomas Pace; Brandon Broome; Obi Osuji; Melinda K. Harman (Advances in Orthopedics)
Due to the known potential for fretting and corrosion at modular junctions in orthopaedic implants, this retrospective study evaluated radiographic and clinical outcomes of 85 primary TKA patients implanted with modular stemmed tibial components and followed up for an average of 82 months. There was low incidence of tibial radiolucent lines, excellent functional outcomes, and no complications associated with stem modularity. The findings were comparable to the historical control study involving 107 TKA with a nonmodular tibial stem design. When using surface cemented tibial components combined with a constrained polyethylene bearing, modular stems appear to be a viable option for primary TKA when adequate fixation and rotational stability are maintained.